The Influence Of Job Satisfaction And Work Discipline On Employee Performance At The Regional Drinking Water Company (PDAM) Tirta Jeneberang Gowa District - Mutiara Nur; Samsul Rizal; Muchriady Muchran (CV. AFDIFAL MAJU BERKAH, 2024)
The aim of this study is to find out the influence of leadership style, supervision and work discipline on the performance of officials in the Civil Occupation and Registration Service of Barru District. The object of this study is all 62 respondents. This research is quantitative research. Data collection techniques are done by means of observation, lifting or questionnaire and documentation. The main variables underlying this study are Leadership Style variables as X1, Supervision as X2, Working Discipline as X3, and Officer Performance as Y. While the technical analysis used in the research uses Validity Test, Reliability Test, Classical Assumption Test and Dual Linear Regression Test using the SPSS 27 program. The results of this study showed a positive relationship between the leadership style (X1) and the employer (Y) with a thitung value -2,627 > ttable 0,250 with a Significant Level of 0,011, supervision (X2) with the performance of the employee (Y), with a Thitung value of 3,408 > table 0,250, with a significant rate of 0,001 and work discipline (X3) that contributed positively to the performance (Y). With a thiting value of 2,243 > t table 0,250 and a significant 0.29 in the Population and Civil Registration Service of the District of Barru.